STUDI LITERATURE: ANALISIS PEMANFAATAN LINGKUNGAN SEBAGAI SUMBER BELAJAR IPS BAGI SISWA SEKOLAH DASAR - Yuliana Putri Aryanti; Laely Kurnia Ramadhani, Andini Dina Aprilia, Eka Nur Aeni, Sekar Jernih Isnaeni, Jefri Lian Tamzis, (CV. ADIBA AISHA AMIRA, 2025)
Education plays an important role in human life and continues to experience rapid changes. In elementary schools, learning often emphasizes memorization rather than deep understanding, so that students have difficulty applying knowledge in everyday life. Social Sciences (IPS) as a relevant subject requires a real-life context to improve learning effectiveness. This study aims to analyze the use of the environment as a source of learning IPS for elementary school students. The method used is Literature Review, with data collection from various sources such as journals and articles from 2020 to 2025. The results of the study show that utilizing the surrounding environment can increase student interaction and make learning more concrete, although many teachers have not linked IPS to the environment. This study is expected to provide new insights for educators in optimizing the IPS learning process in elementary schools.